GELAR AKADEMIK DAN CITRA POLITIK (STUDI KASUS: STRATEGI KEMENANGAN NURDIN ABDULLAH DALAM PEMILIHAN GUBERNUR SULAWESI SELATAN TAHUN 2018) - Muhammad Raihan; Andi Yakub; Gustiana A Kambo (Journal Publicuho, 2023)
This research is a literature study related to the ownership of an academic degree as a political image that can influence voter behavior. According to this study, Nurdin was considered successful in influencing the psychological makeup of voters. Previously, his reputation as a transformational figure was built by many media outlets regarding his performance during his two terms as ruler of Bantaeng Regency (Cangara et al., 2015). The image is then given special identification. Nurdin Abdullah's success was later linked to his academic title as a professor. According to Pierre Bourdieu (1986), this is social capital, which may also include intangible things such as ownership of works of art, educational institutions, and linguistic traditions, where social capital may have symbolic significance and can be exchanged for it (Pantouw, 2012). For example, the symbol of Professor Nurdin Abdullah can be interpreted as meaning that the candidate has credibility and has the potential to become a leader. Educational institutions that have gained credibility in assessing a person's ability to achieve have undoubtedly had a significant impact on this type of meaning (Buchari, 2014: 22).